Symbolization of microcosm and macrocosm relationship in Kirab Gunungan Hasil Bumi in Jepara regency: Ethnography of communication study - Suryadi, Muhammad; Maghfiroh, Alvina (Universitas Ahmad Dahlan, 2025)
Kirab Gunungan Hasil Bumi (KGHB) is a tradition held once a year in Jepara Regency. The contribution of this research is culture preservation for young generation. This study is descriptive qualitative research that uses ethnography of communication’s approach through the communication component analysis scheme by Saville-Troike (2003). Data collection was carried out by participatory observation and in-depth interviews. The data was analyzed by interpretation based on ten communication components: topic, purpose, setting, key, participants, message form, message content, act sequence, rules of interaction, and norms of interpretation. The results of this research show that each component can synergize with the other, which abstracts a masterpiece of gunungan hasil bumi, cooperation values, and spiritual values. Gunungan hasil bumi is a symbol of relationship between humans and nature, and humans to God. Mutual cooperation value is represented in ten communication components in creation of gunungan hasil bumi. The conclusion of this study is the ten communication components that embody a series of traditions of spiritual values and a symbolization of the relationship between microcosm and macrocosm. The design of masterpiece gunungan hasil bumi as a miniature of cultural life of Jepara people that preserved until now.